The Mentoring and Monitoring Practices of Schools District Supervisors - Caayaman, Teresita A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Mentoring and Monitoring are crucial skills of Schools District Supervisors in doing their roles and functions as mandated in Republic Act 9155. However, it has been observed that formal mentoring and monitoring were not yet fully implemented in the Department of Education, Bohol Division, specifically to the Secondary School Principals. On this ground, this study was conducted to assess the mentoring and monitoring practices of Schools District Supervisors in terms of Instructional Leadership and in terms of Curricula Supervision. The study utilized data triangulation in qualitative research to examine three sources of data from the two groups of respondents who were the twenty Full-fledged Schools District Supervisors and twenty-eight Full-fledged Secondary School Principals in the three Congressional Districts in Bohol. Both respondents were conducted an open-ended interview with the same questions while on the documentary data, data from the Schools District Supervisors of their trainings attended were included. The results showed that the mentoring and the monitoring practice of Schools District Supervisors in terms of Instructional Leadership was communicating verbally, while there were no practices revealed for the following: mentoring and monitoring practices of Schools District Supervisors in terms of Curricula Supervision. mentoring and monitoring practices of Schools District Supervisors which are effectively implemented to the Secondary School Principals in terms of Instructional Leadership and in terms of Curricula Supervision, mentoring and monitoring practices of Schools District Supervisors how they are effectively implemented to the Secondary School Principals in terms of Instructional Leadership and in terms of Curricula Supervision These results imply the need to intensify the mentoring and monitoring practices of Schools District Supervisors by creating a policy on it.